Kedudukan Perjanjian Kawin Yang Dibuat Setelah Perkawinan Terhadap Pihak Ketiga - Handayani, Fitri Mindari (CV. Era Digital Nusantara, 2024)
The diversity of religions and beliefs in Indonesia does not rule out the possibility of marriage between followers of religions and beliefs. According to Article 35 and its explanation, as well as Article 37 paragraph (1) of Law Number 23 of 2006 concerning Population Administration which indirectly provides opportunities for interfaith marriages to occur. This type of research is Normative Legal Research by determining legal issues, collecting legal materials, examining legal issues based on the materials that have been collected, drawing conclusions in the form of arguments that answer legal issues. The conclusion of this research is that according to law, interfaith marriages are invalid through the Review of Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law and Islamic law as well as the Constitutional Court Decision Number 71/PUU-XX/2022.